Hieratische Gefäßaufschriften aus dem späten Alten Reich - Seyfried, Karl-Joachim (Zeitschrift für ägyptische Sprache und Altertumskunde, 2014)
A reviewed and enlarged compilation of Old Kingdom hieratic inscriptions written on offering (funerary) vessels – except the well known corpus of the Qubbet el-Hawa samples (approximately 2000 objects) – increases the number of this kind of inscriptions outside the Aswan region up to 95 objects: (a) Tell Edfu: 41; (b) Gebelen: 11; (c) Siut: 3; (d) Meir: 4; (e) Saqqara: 3; (f) Abusir: 1; (g) Giza: 1 and (h) Provenance unknown: 6. To these 70 items collected so far one may add now the 25 items believed to originate from the area of (i) Naqada/Qus in the 5 th Upper Egyptian nome. The publication of these objects forms the core of the contribution. They are housed in the Ägyptisches Museum Berlin and had been bought by Ludwig Borchardt at the end of the 19 th century in Luxor. Some of the inscriptions make use of a formula and expressions not to be faced with commonly. Several individuals mentioned in the “Berlin offering texts” can be identified to some certainty with family members quoted in H. G. Fischers “Inscriptions of the Coptite Nome”.